2016
DOI: 10.3329/ajmbr.v2i2.29075
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of producing summer cauliflower as influenced by organic manures and spacing

Abstract: Abstract:The experiment was conducted to find out the effect of organic manures and spacing on the growth and yield of cauliflower in summer season. In this study, the treatment consisted of three organic manures viz. F 0 : no organic manure, F 1 : cowdung, F 2 : vermicompost and three spacing viz. S 1 (60 × 30) cm, S 2 (60 × 40) cm, S 3 (60 × 50) cm. Two factorial experiments were laid out in the RCBD with three replications. Significant variations in all parameter were observed due to organic manure and spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 4 publications
1
7
3
Order By: Relevance
“…In case of spacing, it was revealed that with the increase in spacing leaf width showed increasing trend. This is due to the fact that in case of closer spacing plant compete for light and with the time being leaf width decreases Similar results were observed by (Shrestha and Thapa, 2018) and (Farzana et al, 2016). Statistically significant variation was recorded due to interaction effect of different levels of nitrogen and spacing in terms of leaf width of cauliflower.…”
Section: Growth Parameterssupporting
confidence: 79%
“…In case of spacing, it was revealed that with the increase in spacing leaf width showed increasing trend. This is due to the fact that in case of closer spacing plant compete for light and with the time being leaf width decreases Similar results were observed by (Shrestha and Thapa, 2018) and (Farzana et al, 2016). Statistically significant variation was recorded due to interaction effect of different levels of nitrogen and spacing in terms of leaf width of cauliflower.…”
Section: Growth Parameterssupporting
confidence: 79%
“…Fertilization applied with each treatment shows a clear positive effect in this study, as the results indicate that cauliflower plants increased in size and yield in all treatments compared to the control (T0, no amendment). On the one hand, it was observed that the number of leaves evaluated in each experimental unit had more than 14 leaves up to a maximum of 26, results that exceed what was previously reported (Farzana et al, 2016). The height and number of leaves of cauliflower plants did not show significant differences between treatments, unlike previous studies in which height and number of leaves did vary as a function of the amendment used (Farzana et al, 2016).…”
Section: Discussioncontrasting
confidence: 62%
“…The technique of using a soil mixture with fertilizer for potted plant cultivation has some advantages compared to using fertilizers in inert substrates, such as perlite and vermiculite, or directly in the soil. For example, it significantly improves the adsorption of fertilizer nutrients and the retention of fertilizers against leaching (Bunt, 1988;Farzana et al, 2016). With this, it is possible to calculate and apply the right doses of nutrients ensuring their availability throughout plant development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crops grow in such close spacing yield more though main heads are smaller and these mature slightly later that case optimum spacing is followed. Rahman et al [3], Farzana et al [21] reported the maximum yield of cauliflower where the plants were spaced 45×50 cm apart.…”
Section: Curd Yield Per Hectarementioning
confidence: 99%